2014
DOI: 10.1155/2014/380424
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C Therapy in Liver Cirrhosis Complicated by Telaprevir-Induced DRESS

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare yet severe adverse drug-induced reaction with up to 10% mortality rate. Recent clinical trials reported an association between DRESS and telaprevir (TVR), an NS3/4A protease inhibitor of chronic hepatitis C (CHC) virus genotype 1. Its diagnosis is challenging given the variable pattern of cutaneous eruption and the myriad internal organ involvement. We present two patients who are middle-aged, obese, and white with CHC cirrhosis. They both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…14,[26][27][28] Cases of SCARs occurred only in TVR group during clinical trials and they were also reported in post registration's studies. 12,14,26,[29][30][31][32][33][34][35] The most common skin rashes reported during the study were characterized as mild or moderate (24 patients -85,72%). The morphological pattern of skin rashes was similar in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…14,[26][27][28] Cases of SCARs occurred only in TVR group during clinical trials and they were also reported in post registration's studies. 12,14,26,[29][30][31][32][33][34][35] The most common skin rashes reported during the study were characterized as mild or moderate (24 patients -85,72%). The morphological pattern of skin rashes was similar in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the secondary cutaneous eruption to these medications presents as a pruriginous, erythematous macule and papule, with fine desquamation, affecting extensor surfaces of members and trunk [ 13 ]. There are reports of drug reaction with eosinophilia and systemic symptoms (DRESS), toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) [ 5 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some diseases such as cryoglobulinemia, polyarteritis nodosa and erythema multiformis are commonly seen in association with hepatitis C [ 10 ]. Skin biopsy is also not specific, but it is important for the differential diagnosis with other causes of vasculitis, infectious exanthemas or autoimmune diseases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe complications related to this therapy included hepatic decompensation, renal failure, severe infections, asthenia, and a variety of hematological abnormalities, including anemia (requiring erythropoietin and/or blood transfusion), neutropenia (requiring granulocyte‐stimulating agent), and thrombocytopenia (requiring thrombopoietin) . Furthermore, patients receiving TVR were at higher risk for experiencing severe cutaneous adverse reactions including drug rash with eosinophilia and systemic symptoms and toxic epidermal necrolysis, as well as anorectal discomfort and pruritus. Patients who underwent TVR‐based triple therapy were at higher risk for SAEs than patients who received a BOC regimen.…”
Section: Safety Outcomesmentioning
confidence: 99%